2016
DOI: 10.1016/j.jvs.2016.06.099
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supervised exercise therapy for intermittent claudication on lower limb lean mass

Abstract: Twelve weeks of standard treadmill-training for intermittent calf claudication did not result in loss of calf LM; however, a significant decrease in bilateral thigh LM was observed, even in patients with unilateral symptoms. Further research on optimum exercise modalities and end points are required to determine the pathophysiology and effects of these changes on function and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The influence of such training on the nutritional status of patients with IC has been poorly addressed in the literature. This is despite the potential consequences associated with increasing metabolic demands through high-intensity exercise without the concurrent administration of adequate nutrition in this already nutritionally vulnerable group [45,46]. In fact, evidence exists to suggest that combined nutrition and exercise interventions in the rehabilitation setting are preferable, with those receiving exercise alone demonstrating greater declines in nutritional status and physical health [47,48,49].…”
Section: Nutrition In the Management Of Peripheral Arterial Diseasementioning
confidence: 99%
“…The influence of such training on the nutritional status of patients with IC has been poorly addressed in the literature. This is despite the potential consequences associated with increasing metabolic demands through high-intensity exercise without the concurrent administration of adequate nutrition in this already nutritionally vulnerable group [45,46]. In fact, evidence exists to suggest that combined nutrition and exercise interventions in the rehabilitation setting are preferable, with those receiving exercise alone demonstrating greater declines in nutritional status and physical health [47,48,49].…”
Section: Nutrition In the Management Of Peripheral Arterial Diseasementioning
confidence: 99%
“…Several studies have even suggested a potentially detrimental effect of attaining the pain threshold. 148 Furthermore, the results of studies investigating exercise training using a submaximal pain threshold seem to be comparable with those of studies involving attainment of the pain threshold. 149e152…”
Section: What Is Not Consensual?mentioning
confidence: 73%
“…However, it should be noted that structured walking exercise alone, as suggested for patients with LEAD [39,40], has little or no effect on muscle loss prevention, while clinically meaningful gains in muscle mass can be achieved by progressive resistance training [41]. In a study conducted by Vun et al, a loss of lean mass of the thighs of the symptomatic as well as asymptomatic leg, after the completion of a standard, treadmill-based, supervised exercise in LEAD patients, was observed [43]. This finding is consistent with the results found in a randomized controlled study where patients lost strength in both limbs after changing from strength to treadmill training [44].…”
Section: Discussionmentioning
confidence: 99%